Factors contribute to absenteeism: A case of manufacturing company in Malaysia (CTRM Aero Composites Sdn. Bhd.) / Farah Hazwani Adnan - Adnan, Farah Hazwani (Faculty of Business Management, 2017)
This research is conducted to carry out a study entitled “Factors Contribute to Absenteeism: A Case of Manufacturing Company in Malaysia (CTRM Aero Composites Sdn Bhd)”.This study was conducted in order to find out the significant relationship between the independent variables with the dependent variable. The dependent variable is absenteeism of employees in organization. The independent variables in this study are flexible working hour, pay and stress. The sample size used for this study is 190. Data was obtained through convenience sampling. All data were analyzed and interpreted by using Statistical Package for the Social Science (SPSS) software. Thus, Pearson Correlation analysis indicates the strength of association of flexible work hour and stress is high while pay is negligible. Apart from that, regression analysis shows there is positive and significant relationship between stress and absenteeism while negative and significant relationship between flexible working hour and absenteeism. Lastly, pay shows no significant relationship with absenteeism.